Did the Healthcard Program ensure Access to Medical Care for the Poor during Indonesia's Economic Crisis? - Menno Pradhan; Fadia Saadah; Robert Sparrow (Tinbergen Institute, 2003)
The Indonesian Healthcard program was implemented in response to the economiccrisis, which hit Indonesia in 1998, in order to preserve access to health care servicesfor the poor. The Healthcard provided the households with subsidised care at publichealth care providers, while the providers themselves received budgetary support tocompensate for the extra demand. This papers_new looks at the impact of this program onoutpatient care utilisation, and, in particular, endeavours to disentangle the directeffect of the allocation of Healthcards from the indirect effect of the transfer of fundsto health care facilities. It finds that the program resulted in a net increase inutilisation for the poor beneficiaries. Por non-poor beneficiaries the program resultedin a substitution from private to public providers only. However, the largest effect ofthe program seems to have come from a general increase in the quality of publicservices resulting from the budgetary support they received through this program.
Keywords: 330; health insurance; program evaluation; targeted price subsidies; Indonesia; Gesundheitsversorgung; Armut; Gesundheitspolitik; Wirkungsanalyse; Indonesien